At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
- 0.6
Step-by-step explanation:
Start point: (5,6)
End point: (-5,12)
rate of change = (12-6) / (-5-5) = 6/-10 = - 3/5 = - 0.6
Answer:
The rate of change is -0.6
Step-by-step explanation:
Given
[tex](x_1,y_1) = (5,6)[/tex]
[tex](x_2,y_2) = (-5,12)[/tex]
Required
Determine the rate of change
The rate of change means the slope (m) and it is calculated as thus:
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
[tex]m = \frac{12-6}{-5-5}[/tex]
[tex]m = \frac{6}{-10}[/tex]
[tex]m = -\frac{6}{10}[/tex]
Simplify the fraction
[tex]m = -\frac{3}{5}[/tex]
[tex]m=-0.6[/tex]
The rate of change is -0.6
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.